INSPIRING THE STUDENTS TO LEARN ENGLISH FROM INTRINSIC ELEMENTS AND MORAL VALUES DEPICTED IN THE MOVIE ENTITLED â€œMOWGLI: LEGEND OF THE JUNGLEâ€ DIRECTED BY: ANDY SERKIS - Nia Yulia; Baginda Simaibang; Hanni Yukamana (Esteem Journal of English Education Study Programme, 2022)
This research aimed at describing and analysing intrinsic elements and moral values depicted in the movie â€œMowgli: Legend of the Jungleâ€ directed by Andy Serkis. Content analysis method was used in doing this research. Method of data collecting is by watching the movie, and then the data were analysed by using triangulation: movie, interview and book review. Based on the findings of the study, the intrinsic elements that are participating informing a story of the movie consist of character, setting, plot, theme or statement and subject matter. While there are 7 moral values that can be depicted through the movie. They are love and affection, struggle, kindness, courage, bravery, wisdom and strong believe. The most dominant one is bravery. By Analysing the elements and the moral values of the movie, hopefully will build a good character for students and also will give them inspiration that learning English by watching movie is more enjoyable than learning through book.